Loss of the selective autophagy receptor p62 impairs murine myeloid leukemia progression and mitophagy - Nguyen, The Duy; Haberbosch, Isabella (Blood, 2019)
Abstract - Autophagy maintains hematopoietic stem cell integrity and prevents malignant transformation. In addition to bulk degradation, selective autophagy serves as an intracellular quality control mechanism and requires autophagy receptors, such as p62 (SQSTM1), to specifically bridge the ubiquitinated cargos into autophagosomes. Here, we investigated the function of p62 in acute myeloid leukemia (AML) in vitro and in murine in vivo models of AML. Loss of p62 impaired expansion and colony-forming ability of leukemia cells and prolonged latency of leukemia development in mice. High p62 expression was associated with poor prognosis in human AML. Using quantitative mass spectrometry, we identified enrichment of mitochondrial proteins upon immunoprecipitation of p62. Loss of p62 significantly delayed removal of dysfunctional mitochondria, increased mitochondrial superoxide levels, and impaired mitochondrial respiration. Moreover, we demonstrated that the autophagy-dependent function of p62 is essential for cell growth and effective mitochondrial degradation by mitophagy. Our results highlight the prominent role of selective autophagy in leukemia progression, and specifically, the importance of mitophagy to maintain mitochondrial integrity.
Gesehen am 24.04.2019